1975
DOI: 10.1037/h0076566
|View full text |Cite
|
Sign up to set email alerts
|

Life-span stability in olfactory sensitivity.

Abstract: Assessed the olfactory acuity of 120 6-94 yr olds by means of magnitude production in a simple motor task. 7 concentrations of n-propanol, ranging from 100 to 1.56%, served as odorants. Remarkable consistency across concentrations was found in Ss of all ages, those in the younger and older age groups generating the most similar functions. Evidence of olfactory decline in the oldest Os was lacking, suggested only by the greater incidence of nonresponse at weaker concentrations in the intermediate 40-50 yr group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
2

Year Published

1976
1976
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 26 publications
(28 reference statements)
1
19
2
Order By: Relevance
“…Literature on the effect of aging on suprathreshold measures of odors is somewhat mixed in results. Some studies showed diminished intensity ratings with age (Stevens et al 1982;Stevens and Cain 1985;Wysocki and Gilbert 1989), while others did not see the effect (Rovee et al 1975;Cowart 1989). Discrepancies between the current and other studies can be explained by differences in study population, odorants tested, and experimental procedures.…”
Section: Variation In Retronasal Odor Responsiveness Among Individualscontrasting
confidence: 74%
“…Literature on the effect of aging on suprathreshold measures of odors is somewhat mixed in results. Some studies showed diminished intensity ratings with age (Stevens et al 1982;Stevens and Cain 1985;Wysocki and Gilbert 1989), while others did not see the effect (Rovee et al 1975;Cowart 1989). Discrepancies between the current and other studies can be explained by differences in study population, odorants tested, and experimental procedures.…”
Section: Variation In Retronasal Odor Responsiveness Among Individualscontrasting
confidence: 74%
“…In the present work, such recruitment could include fibers from free nerve endings of the trigeminal nerve that are distributed throughout the nasal mucosa, since amyl acetate is known to have trigeminal stimulative properties at higher concentrations and receives intensity ratings from anosmics similar to those observed in normosmics (Doty et aI., 1978). Such a notion may explain why some suprathreshold scaling parameters are insensitive to changes in the ability to smell related to age and Alzheimer's disease (e.g., Green et aI., 1989;Rovee, Cohen, & Shlapack, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the well-established age-related alterations in olfactory function were completely missed in one study that employed rating scales, leading to the erroneous conclusion that olfaction is largely impervious to agerelated changes (Rovee et al 1975).…”
Section: Rating Scalesmentioning
confidence: 99%